Advancing reputation measurement: evolving toward improved quantitative assessments. Issue 2 (24th July 2019) - Horn, Richard; Wagner, Ralf
Abstract : Purpose: The purpose of this paper is to provide evidence on the information-gathering deficits in contemporary reputation measurement that are rooted in sampling and to obtain supporting information from respondents from various stakeholder groups. Design/methodology/approach: In regard to social emergence theory, the authors examine the common practice of aggregating reputational judgments from randomly sampled respondents without considering their knowledge domains. A stereotyping experiment conducted in three countries provides evidence that lower-level reputations might vary, whereas higher-level reputations resulting from the social emergence process do not vary. Findings: The findings demonstrate that researchers should consider respondents' heterogeneity in regard to reputation measurement. Stakeholder judgments divergent from their domains of expertise often add noise, instead of informative answers, to the reputational categories. Research limitations/implications: The social emergence process, in addition to the roles of the stakeholders, their interaction structures and the timing of their communication, needs to be incorporated into an improved reputation measurement method. Practical implications: Not all information from the same respondent should be considered when computing a final reputation score. Respondents' heterogeneity is revealed to be fundamental for reputational assessments. Originality/value: This study is original in its examination of the validity of reputation assessment being restricted to lower-level descriptions of the supervenience relation. Building upon the results of the experiment conducted in three national framings, this paper suggests ways to improve reputation measurement.